میتافۆری نەخۆشییەکان لە زمانی کوردیدا "شێرپەنجە بە نموونە" - حەمەغەریب, د. هێرۆ ئەحمەد (Sulaimani Journal for Humanities, 2023)
This study aims to examine Metaphors of Diseases in the Kurdish language – Cancer as an Example, in which the use of cancer as a metaphor in the media in the Central Kurdish dialect is investigated on the Internet from social networks from people's views and their metaphorical expressions in this field, most of which fall between 1/1/2020 to 1/1/2 2023. The researcher's own experience in this field and linguistic taste can be used as research data. The paper focuses on the role of metaphor in constructing our experience of cancer and identifying which metaphors play more of a role in this area. It focuses on the role and power of metaphor in building our experience of this disease and the positive and negative psychological effects of different uses of metaphors in Kurdish society. It examines the impact of these expressions, not only for their context in the public but also for their role in changing the perception of the individual, then society, of diseases in general and cancer in particular. The content of the study, in addition to the summary and list of sources, consists of: (an introduction, two sections, and results obtained). The first section is devoted to the conceptualization of metaphor and the linguistics of perception in general. The theoretical framework and linguistic characteristics include conceptual metaphors; it examines the identification and classification associated with cancer metaphors of illness; and finally, the commonly used conceptual metaphors associated with cancer. In the second part, the metaphor of cancer in the media is presented, for this purpose, relying on significant data and examples in the Kurdish media as mentioned above. the research falls into the field of "cognitive linguistics", based on Lakoff and Johnson's conceptual metaphor theory (1980) as a basis for work.
Keywords: میتافۆر کەلتوور شێرپەنجە جەنگشەڕ زمانەوانیی درکپێکردن ئاوەز ڕاگەیاندن